Pondok Modern Dan Pembelajaran Membaca Kitab Kuning; Studi Pelaksanaan Di Pesantren Ar-Raudlatul Hasanah, Medan, TA 2018-2019 - R Rasyidin; Mukhlis Mubarrak Dalimunthe; Abdullah Sani Ritonga (Jurnal Penelitian Medan Agama, 2020)
The transformation of education in the world of Pesantren, from traditional to modern, is a bit of a question of impact on the system, institutional, and curriculum. Among the consequences is a shift in the important position of the yellow book. Modern boarding schools are considered to be focusing on learning about them and focusing too much on learning About Arabic for conversation. This research aims to find a complete picture of the actual tradition of yellow book learning still valid in pesantren, despite its modern typology. Located at Pesantren Ar-Raudlatul Hasanah, Medan, research conducted through observation, interview and document studies with miles-huberman analysis method found that the study of yellow book in Ar-Raudlatul Hasanah boarding school through three stages; (1) classical mastery of tool science, (2) basic training stage through study groups, and (3) applicative stage in fath al-Kutub program for final class students. With such a picture, this research is expected to contribute a wealth of yellow book learning design in pesantren that can be applied in other pesantren institutions.